1998
DOI: 10.1164/ajrccm.158.1.9712053
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Supplementation and Respiratory Functions among Workers Exposed to High Levels of Ozone

Abstract: Ozone exposure has been related to adverse respiratory effects, in particular to lung function decrements. Antioxidant vitamins are free-radical scavengers and could have a protective effect against photo-oxidant exposure. To evaluate whether acute effects of ozone on lung functions could be attenuated by antioxidant vitamin supplementation, we conducted a randomized trial using a double-blind crossover design. Street workers (n = 47) of Mexico City were randomly assigned to take daily a supplement (75 mg vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(71 citation statements)
references
References 26 publications
2
69
0
Order By: Relevance
“…In support of this contention recent field studies have demonstrated that increased intakes of nutritional antioxidants can reduce the magnitude of lung function decrements in subjects exposed to high ozone doses both occupationally (shoe cleaners in Mexico City [38]) and recreationally (Dutch cyclists [39]). In these studies protection was observed after prolonged periods of supplementation (75 mg vitamin E, 650 mg vitamin C, 15 mg b-carotene, daily for 1.5 months in the Mexico City study; 100 mg vitamin E, 500 mg vitamin C daily for 15 weeks in the Dutch cyclist study) against average ozone backgrounds of 67.3 parts per billion (ppb) and 38.5 ppb respectively.…”
Section: Respiratory Tract Lining Fluid Antioxidants and Air Pollutionmentioning
confidence: 94%
See 1 more Smart Citation
“…In support of this contention recent field studies have demonstrated that increased intakes of nutritional antioxidants can reduce the magnitude of lung function decrements in subjects exposed to high ozone doses both occupationally (shoe cleaners in Mexico City [38]) and recreationally (Dutch cyclists [39]). In these studies protection was observed after prolonged periods of supplementation (75 mg vitamin E, 650 mg vitamin C, 15 mg b-carotene, daily for 1.5 months in the Mexico City study; 100 mg vitamin E, 500 mg vitamin C daily for 15 weeks in the Dutch cyclist study) against average ozone backgrounds of 67.3 parts per billion (ppb) and 38.5 ppb respectively.…”
Section: Respiratory Tract Lining Fluid Antioxidants and Air Pollutionmentioning
confidence: 94%
“…No protection against ozoneinduced airway inflammation was reported. In this study [38,39,42]. Whilst these studies examined responses in healthy subjects, a recent study by TRENGA et al [43] addressed whether vitamin supplementation (500 mg vitamin C; 400 IU (264 mg) vitamin E daily for 4 weeks) would protect asthmatics against ozone-induced (120 ppb for 45 min, with mild exercise) lung function decrements and following subsequent provocation with sulphur dioxide (SO 2 ) (100 and 250 ppb).…”
Section: Respiratory Tract Lining Fluid Antioxidants and Air Pollutionmentioning
confidence: 99%
“…In these studies, healthy adults were randomised to receive vitamin C (650 mg), vitamin E (75 mg) and b-carotene (15 mg) for several weeks [80,[93][94][95]. More recently, a study of asthmatic children exposed to high levels of air pollutants in Mexico City also suggested that supplementation with vitamin C (250 mg?day -1 ) and vitamin E (50 mg?day -1 ) had a modulating effect on acute lung function changes [96].…”
Section: Antioxidant Supplementationmentioning
confidence: 99%
“…1 A number of studies on the acute health effects of O 3 exposure in Mexico City have been performed. [2][3][4][5][6] In several of these investigations, ambient O 3 concentrations measured at fixed sampling sites have been used to assign exposure to the individuals under study. How well such area measurements reflect actual individual O 3 exposures is an important question for environmental epidemiology, and several comparisons of ambient with personal concentrations have been conducted in other regions of the world.…”
Section: Introductionmentioning
confidence: 99%